2016
DOI: 10.1177/0149206316672531
|View full text |Cite
|
Sign up to set email alerts
|

When Wanting To Be Fair Is Not Enough: The Effects of Depletion and Self-Appraisal Gaps on Fair Behavior

Abstract: Ensuring that managers engage in fair behaviors is critical for the effective functioning of organizations. Previous research has focused on increasing the enactment of interactional justice (i.e., justice as a dependent variable) by enhancing managers’ willingness to be fair. Drawing upon the limited strength model of self-regulation, we argue that the enactment of interactional justice may not depend solely on managers’ willingness or motivation but also on the extent to which managers have the self-regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 80 publications
1
32
0
Order By: Relevance
“…Restructured FOR training may also outperform typical FOR training regarding outcomes in nontraining contexts. For instance, the restructured information presentation facilitates an adoption of a common evaluation standard without an effortful process of feedback and correction, which may conserve organizational leaders' energy to regulate their behavior and subsequently increase an enactment of interactional justice between these leaders and their followers (Whiteside & Barclay, ). Compared with typical FOR training, restructured FOR training may also significantly increase perceptions of procedural justice regarding performance appraisal through the increased accessibility of the information about the appraisal criteria (Erdogan, Kraimer, & Liden, ).…”
Section: Discussionmentioning
confidence: 99%
“…Restructured FOR training may also outperform typical FOR training regarding outcomes in nontraining contexts. For instance, the restructured information presentation facilitates an adoption of a common evaluation standard without an effortful process of feedback and correction, which may conserve organizational leaders' energy to regulate their behavior and subsequently increase an enactment of interactional justice between these leaders and their followers (Whiteside & Barclay, ). Compared with typical FOR training, restructured FOR training may also significantly increase perceptions of procedural justice regarding performance appraisal through the increased accessibility of the information about the appraisal criteria (Erdogan, Kraimer, & Liden, ).…”
Section: Discussionmentioning
confidence: 99%
“…We have claimed that justice enactment is in essence about self-reported justice enactment, which is not to say that these are necessarily true perceptions, but neither are subordinates' justice perceptions. In an experimental study with students, Whiteside and Barclay (2018) investigated differences between self-reported and other-coded justice enactment during a layoff and noted self-appraisal gaps when students had depleted resources. In another study, it was found that the justice climate perceived by subordinates is impacted by supervisors' own perceptions of justice from their superiors, suggesting that justice enactment from supervisors towards their employees is impacted by supervisors' own treatment (Ambrose et al, 2013).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The existing studies on antecedents of self-reported justice enactment can be differentiated into two areas: those pertaining to trait-like aspects of the supervisor and those referring to how the supervisor views the subordinate. Regarding the first area, managers have been found to report higher self-reported justice enactment when they express higher moral identity (Brebels et al, 2011), view themselves as ethical leaders (Long, 2016), and have a good capacity for perspective-taking (Whiteside & Barclay, 2018). As concerns the second area, research has found managers to report higher adherence to justice rules when they rate their subordinates as having a higher need for belonging (Cornelis et al, 2013), like and trust their subordinates, and have high-quality relationships with them (Huang et al, 2017;Koopman et al, 2015;Zhao et al, 2015).…”
Section: Antecedents Of Self-reported Justice Enactmentmentioning
confidence: 99%
See 2 more Smart Citations